1998
DOI: 10.1097/00042560-199807010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Release of Metalloproteinase-9 (92-kd Type IV Collagenase) by Kaposi's Sarcoma Cells

Abstract: Kaposi's sarcoma (KS) is an angioproliferative disease characterized by proliferating spindle-shaped cells, angiogenesis, and inflammatory cell infiltration. Several lines of evidence suggest that KS is a multifocal cytokine-mediated disease of vascular origin. Because metalloproteinases (MMPs) are important enzymes involved in angiogenesis, we studied their activity in five different KS-derived cell lines and compared these data with those obtained with human umbilical vein endothelial cells (HUVEC). We focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 35 publications
9
32
0
Order By: Relevance
“…Western blots usually failed to resolve the three isoforms of the MMPs because of the diffusion of the proteins during transfer from gels to the membranes. 6 hpi, which peaked at 24 hpi and was sustained for up to 48 hpi (Fig. 4C).…”
Section: Kshv Infection Enhances Huvec Invasion Of the Extracellular mentioning
confidence: 92%
See 1 more Smart Citation
“…Western blots usually failed to resolve the three isoforms of the MMPs because of the diffusion of the proteins during transfer from gels to the membranes. 6 hpi, which peaked at 24 hpi and was sustained for up to 48 hpi (Fig. 4C).…”
Section: Kshv Infection Enhances Huvec Invasion Of the Extracellular mentioning
confidence: 92%
“…A number of MMPs, including MMP-1, -2, -3, -9, and -19, have been detected in KS tumor cells, implicating their roles in the pathogenesis of these tumors (6,23,29,42). Indeed, an inhibitor of MMPs, COL-3, had an overall 44% response rate in AIDS-KS patients.…”
mentioning
confidence: 99%
“…Of these cytokines, IL-2, tumor necrosis factor alpha, and IFN-␥ are elevated in KD. Furthermore, pro-MMP-9 levels have been demonstrated to be elevated in certain viral infections, most notably those caused by retroviruses and herpesviruses (2,8,9,19,33). Recently, Takeshita and colleagues suggested that the acutephase response to lipopolysaccharide may be involved in the pathogenesis of KD, supporting the thesis that KD may have an infectious and/or postinfectious etiology (36).…”
Section: Vol 10 2003 Elevated Pro-mmp-9 and Timp-1 In Kd 311mentioning
confidence: 96%
“…19,22 In addition, KS-derived cells constitutively release matrix metalloproteinase 9 (MMP-9). 23 KSHV encodes for many proteins, and some of these are involved in cell proliferation and the up-regulation of angiogenesis. The viral G protein-coupled receptor (vGPCR) is a homolog of the human IL-8 receptor that induces expression of mitogenic and angiogenic growth factors including VEGF.…”
Section: Introductionmentioning
confidence: 99%